KHAZANAH budaya lokal Sebuah pengantar untuk memahami kebudayaan daerah di Nusantara Gatut Murniatmo...[et al] ; penyunting, Hermawan H. Nugroho, Sjamsu Dradjat. - Gatut Murniatmo; Hermawan H; Nugroho; Sjamsu Dradjat (Aditya Karya Nusa, 2000)
302 hlm. ilus. 24 cm (3 eks.)